The Factors Affecting Buyer Interest In Indomaret Retail In Maros City - Mulbi, Buhari; Ramli, Anwar (Archives of Business Research, 2019)
This study aims to determine 1) the effect of prices on buyer interest in Indomaret, 2) the effect of product quality on buyer interest in Indomaret and 3) the effect of location on buyer interest in Indomaret, Maros City. The object of this research is consumers who shop at Indomaret, Maros City. This type of research is explanatory descriptive research, namely to know and explain the characteristics of the variables under study in a situation. The sampling technique uses accidental sampling techniques, namely anyone who accidentally meets with a researcher can be used as a sample, with 97 respondents. The analytical method used is the multiple regression method with the help of the SPSS 25 program. The results of this study indicate that, prices have a positive and significant effect on buyer interest in Indomaret, Maros City. Then the product quality has a positive and significant effect on the interest of buyers in Indomaret, Maros City, and the location has a positive and significant effect on buyer interest in Indomaret in the City of Maros.